Addressing contemporary threats in anonymised healthcare data using privacy engineering - Sanjiv M. Narayan; Nitin Kohli; Megan M. Martin (npj Digital Medicine)
Abstract Cyber-attacks on healthcare entities and leaks of personal identifiable information (PII) are a growing threat. However, it is now possible to learn sensitive characteristics of an individual without PII, by combining advances in artificial intelligence, analytics, and online repositories. We discuss privacy threats and privacy engineering solutions, emphasizing the selection of privacy enhancing technologies for various healthcare cases. Future solutions must consider dynamic flows of data throughout their lifecycle.